Proceso de atención de enfermería en neonato de 7 días con sífilis congénita. - Muñoz Aguilar, Thalía Rosalía (2021)
Syphilis is a serious pathology that occurs in people and is transmitted through sexual, blood and perinatal routes, since it can be asymptomatic or symptomatic and also cause harm to the individual. In Ecuador, the Ministry of Public Health has requested diagnostic tests to be carried out in health centers to detect a pregnant woman with syphilis in time to treat the disease and to avoid the morbidity and mortality associated with congenital syphilis. Congenital syphilis is an infection that is transmitted to the fetus through the placenta, in Ecuador 70% of mothers who have not received treatment for syphilis during pregnancy have caused it to present certain clinical manifestations such as: abortions, premature births, delayed intrauterine growth, intrauterine fetal death, and in the newborn skin lesions, bone lesions, alterations in the dentition. This pathology is classified into two phases: early congenital syphilis and late congenital syphilis, depending on the time of onset. Women with syphilis who do not attend the health center to receive adequate prenatal care has been one of the reasons why the fetus develops congenital syphilis. It is very important to inform the mother that after the birth of the newborn, it should receive timely treatment to avoid severe damage to the newborn. As a health professional, it is of utmost importance to apply the nursing care process in the Newborn with congenital syphilis to discover the priorities and to be able to provide adequate care without forgetting the correct use of biosafety measures.